Information visualization : perception for design - Ware, Colin (Interactive technologies., 2012)
Information Visualization: Perception for Design is a comprehensive guide to what the science of human perception tells us about how we should display information. The human brain is a super-computer for finding patterns in information. Our understanding of visual data and visual information is greatly enhanced or impeded by the way information is presented. It is essential that visual data be designed in such a way that key information and important patterns will stand out. It is only by understanding how perception works that the best visualizations can be created. Colin Ware outlines the key principles for a wide range of applications and designs, providing designers with the tools to create visualizations of improved clarity, utility and persuasiveness. The book continues to be the key resource for practical design guidelines, based on perception, which can be applied by practitioners, students and researchers alike. Complete update of the recognized source in industry, research, and academic for applicable guidance on information visualizing. Includes the latest research and state of the art information on multimedia presentation. More than 160 explicit design guidelines based on vision science. A new final chapter that explains the process of visual thinking and how visualizations help us to think about problems. Packed with over 400 informative full color illustrations, which are key to understanding of the subject.